2005
DOI: 10.1029/2004ja010900
|View full text |Cite
|
Sign up to set email alerts
|

Large‐scale variations of the low‐latitude ionosphere during the October–November 2003 superstorm: Observational results

Abstract: [1] The GPS-derived total electron content (TEC), ion drift measurements from the ROCSAT-1 spacecraft at around 600 km altitude, and far-ultraviolet airglow measured by the Global Ultraviolet Imager (GUVI) carried on board the NASA TIMED satellite are utilized for studying large disturbances of the low-latitude ionosphere during the October-November 2003 superstorm period. Two chains of GPS receivers, one in the American sector ($70°W) and the other in the Asian/Australian sector ($120°E), are used to simultan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
118
0

Year Published

2006
2006
2016
2016

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 76 publications
(128 citation statements)
references
References 56 publications
10
118
0
Order By: Relevance
“…The large gradients observed in the VTEC in the southern Brazil and some of the Argentinean stations are due to the geomagnetic storm that has moved the plasma away from the magnetic equator. Lin et al (2005) have reported similar results during the October-November 2003 superstorm periods. They have reported from the GPS-TEC measurements that the equatorial ionospheric anomaly (EIA) expanded to very high latitudes with large increases of TEC after the storm started.…”
Section: Resultssupporting
confidence: 73%
See 1 more Smart Citation
“…The large gradients observed in the VTEC in the southern Brazil and some of the Argentinean stations are due to the geomagnetic storm that has moved the plasma away from the magnetic equator. Lin et al (2005) have reported similar results during the October-November 2003 superstorm periods. They have reported from the GPS-TEC measurements that the equatorial ionospheric anomaly (EIA) expanded to very high latitudes with large increases of TEC after the storm started.…”
Section: Resultssupporting
confidence: 73%
“…Several investigators Y. Sahai et al: Observations of the F-region ionospheric irregularities during "Halloween Storms" have studied the response of the ionospheric F-region in the equatorial and mid-latitude regions during the October 2003 Halloween storms (e.g., Basu et al, 2005Basu et al, , 2007Foster and Rideout, 2005;Lin et al, 2005;Zhao et al, 2005;Sahai et al, 2005;Yizengaw et al, 2005;Chi et al, 2005;Batista et al, 2006;Garner et al, 2006;Abdu et al, 2007Mannucci et al, 2008;Perevalova et al, 2008;Verkhoglyadova et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Some of the energy deposited during the main phase convects to subauroral latitudes as traveling atmospheric disturbances (TADs) that alter the thermospheric density and composition (Lin et al, 2005) at mid-to low latitudes. Observationally, TADs take ∼4 h to propagate from auroral to equatorial latitudes (Bruinsma and Forbes, 2007).…”
Section: Summary and Discussionmentioning
confidence: 99%
“…Moreover, there is a negative temporal trend in the topside ionospheric temperature and density. This is due to a poststorm enhancement of the equatorial ionization anomaly (Lin et al, 2005). The 5 November day looks relatively quiet.…”
Section: Background Problemmentioning
confidence: 99%
“…Geomagnetic storms perturb strongly the entire ionosphere (e.g. Basu et al, 2001;Lin et al, 2005;Mannucci et al, 2005;Yizengaw et al, 2005), such that the ion temperature, density and velocity variations become irregular and grow to hundreds of percents in comparison with the prestorm conditions. Accurate determination of the ionospheric background conditions is required for the identification and numerical estimation of the solar radiation impact.…”
Section: Datamentioning
confidence: 99%